Information Provision and Patient Reported Outcomes in Patients with Metastasized Colorectal Cancer: Results from the PROFILES Registry - Husson, Olga (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Patients with metastasized colorectal cancer (mCRC) have different information needs compared with patients with nonmetastatic colorectal cancer (CRC). Appropriate information provision leads to better patient reported outcomes for patients with nonmetastatic disease. OBJECTIVE: To measure the perceived level of, and satisfaction with, information received by patients with mCRC as compared with those with nonmetastatic (stage I,II,III) CRC. Also, associations of information provision with health status, anxiety, depression, and illness perceptions were investigated. METHODS: A cross-sectional population-based survey was conducted. All CRC patients diagnosed between 2002 and 2007 according to the Eindhoven Cancer Registry (ECR) were selected. Response rate was 75% (n=1159, of which 139 had mCRC). Participants completed questionnaires on information provision (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-INFO25), health status (Short Form-36), anxiety and depression (Hospital Anxiety and Depression Scale [HADS]), and illness perceptions (Brief Illness Perception Questionnaire [B-IPQ]). RESULTS: The perceived receipt of information was quite comparable between CRC patients with and without mCRC. Only perceived receipt of treatment information was higher for patients with mCRC (45 versus 37; p<0.01). Sixty percent of the patients with mCRC were satisfied with the amount of received information and almost 30% wanted to receive more information. The perceived receipt of more disease information and information about other services was associated with worse health outcomes, whereas satisfaction with the received information was not associated with health outcomes CONCLUSION: The findings of this study indicate that some improvements can be made in the provision of information to patients with mCRC. Adequate assessment of information needs of mCRC patients, as well as appropriate responses to these needs by providing the information in an appropriate way could possibly lead to improvements in patient satisfaction.